IMAGINATION OF RELIGION AND POLITICS IN MEDIA ERA POST-TRUTH - Zuly Qodir (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Abstrak. Artikel ini hendak menjelaskan tentang pemberitaan yang terkait Islam di Media mainstream Barat. Pemberitaan di media mainstream barat cenderung negative. Islam itu identic dengan musuh peradaban. Artikel ini berasumsi bahwa pemberitaan negative tentang Islam di Barat dikarenakan adanya tindakan-tindakan yang dilakukan oleh sebagian kelompok migran muslim yang kurang dapat berhubungan dengan baik sesama anggota masyarakat di Barat. Pada era post Truth pemberitaan media tentang Islam sebenarnya dipengaruhi persoalan kepentingan ekonomi dan politik dari kebijakan media. Pemberitaan media tentang Islam merupakan hal yang sangat kompleks tidak hanya dapat dilihat dalam perspektif yang tungal. Artikel ini mempergunakan pendekatan kritis atas perspektif yang digunakan oleh media-media Barat mainstream ketika memberitakan muslim di Eropa. Jika pada persoalan agama dan politik maka media Barat harus dilihat bagaimana mendidik agar kita menjadi “melek media” bagi kalangan masyarakat. Abstract. This article asserts that the imagination of religion and politics in the era of post-truth media can be said to be negative. Religion and politics are mutually antagonistic. Even among supporters of political forces hostile to each other due to religion. This paper provides an explanation that due to media portrayals, especially the foreign media about the impact of Islam is worrying enough in the era of post-truth. Media portrayals of religion and politics are negative then the public needs to get a reinforcement-strengthening (media literacy) relating to religion and politics in the era of post-truth. This article also explains that there is a fairly complex problem when the media provides related depictions of religion and politics, especially related to Islam in the spotlight in the international media and the mainstream media. This article is not directly about to give a critique of the media portrayal of the religion (Islam) in particular and the world of politics going on, because the adherents of a religion does not necessarily become enemies of each other. If you bring religion and politics as the enemy that happens is the commodification religion and politics by the media so that the media does not educate people but just a mere profiteering.